Immunotherapy: Current indications and recommendations in the management of ocular allergy - Padukudru Anand Mahesh; Shambo Samrat Samajdar; Sowmya Arudi Nagarajan; Greeshma Mandya Venkatesh Murthy; Saibal Moitra (Indian Journal of Ophthalmology)
Allergic diseases, including allergic conjunctivitis (AC), pose a significant health burden, affecting both developed and developing nations. Despite its importance, AC is often underreported, leading to underestimated incidence and prevalence. The coexistence of AC with allergic rhinitis and its comorbidity with asthma underscore its clinical relevance. The prevalence of nasal symptoms with eye symptoms related to eye allergy varies among different age groups and regions worldwide. Climatic factors, aeroallergens, and environmental exposure play significant roles in the prevalence of ocular allergies. Allergen immunotherapy (AIT) represents the only disease-modifying treatment for IgE-mediated allergic diseases. This review provides a comprehensive overview of the history, mechanisms, and evidence of AIT for ocular allergies, with a focus on AC. The primary routes of AIT, subcutaneous immunotherapy (SCIT), and sublingual immunotherapy (SLIT) are discussed in detail. The evidence for AIT in treating AC is extensive and demonstrates its effectiveness in alleviating ocular symptoms, reducing medication usage, and improving the quality of life in patients. Both SCIT and SLIT have shown positive results, with SLIT having a more favorable safety profile. Considerations for initiating and maintaining AIT, including adherence, financial burden, and treatment duration, are highlighted. In summary, AIT is a valuable treatment option for AC, offering long-term symptom relief and potential cost-effectiveness. By understanding the history, mechanisms, and evidence of AIT, healthcare providers can better manage ocular allergies and improve patient outcomes.